How does Financial Reporting Quality Relate to Stock Price Crash Risk? Evidence from Indonesian Listed Companies - Butar Butar, Sansaloni; Murniati, Monika Palupi (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
This study examines the influence of financial statement transparency, institutional investor stability, audit tenure, and conservatism on stock price crash risk. Using firms listed on the Indonesia stock exchange from 2011 to 2015 as research samples, 748 firm-year observations are available for data analysis and hypotheses tests. Employing multiple regressions analysis, the results show that institutional investor stability, audit tenure, and conservatism have a significant effect on stock price crash risk. However, a positive association between audit tenure and stock price crash risk is not supported in this study. Meanwhile, the transparency of financial statements has no significant effect on stock price crash risk. It may indicate that Indonesian investors tend to overlook the issues of financial report transparency while making equity investment decisions.